The excavation of the Roman villa in Gadebridge Park, Hemel Hempstead, 1963-8 - Neal, David S. (Reports of the Research Committee of the Society of Antiquaries of London, 1974)
This is an account of excavations of the Roman villa in Gadebridge Park, Hemel Hempstead, which took place in 1963-8. It describes the history of a villa from its simple beginnings in the first century A.D. to its heyday in the fourth century when the owner could boast one of the largest villa bath houses and a bathing pool comparable in size to the Great Bath at Bath. In the mid-fourth century disaster struck. The coin evidence shows that the villa came to an abrupt end and that in or about A.D. 353 it may have been demolished as a result of reprisals against the owner for his support of the rebellion by Magnentius.